An Evaluation of issuing palestinian currency - Al Alem, Laith Nusir Ahmed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: This research is based on the subject of ‘The Importance of Palestinian currency issuance in Palestinian state and its urgent need to stabilize its economy in numerous manners.’ The issuance of Palestinian currency is one of the most critical and sovereignty matters for the Palestinian people while it’s still dealing with various other currencies such as USD, NIS, Euro and Jordan Dinar, etc. This study reveals the factors, reasons, hurdles of the failure of Palestinian economy in currency matter and how this currency matter reflects on the overall economic development of Palestine. After the deep study and analysis it is still recommended that this subject needs further research and examination that focus on studying the Palestinian economy as the subject touches the components of the Palestinian economy particularly under the Israeli occupation, the resulted obstacles and accords that hinder the development of the Palestinian economy and deprives the people from progress, stability and development. To clarify this subject for the readers, it has been necessary to present a brief history of the Palestinian Monetary System to understand the following terms: First: The extent of the availability of factors, economic and financial conditions as well as the basic components related to the process of issuing the Palestinian national monetary. Second: Knowing the fears and warnings that hinder the process of issuing the Palestinian monetary. Third: Identifying the monetary policies in Palestine during the Israeli imperative period from one aspect and during the Palestinian National Authority system in other aspect. In this study, researcher presented the most important points that assure the lack of certain factors such as the financial and economical, and in addition to the components of issuing the Monetary of Palestine under the Israeli occupation while controlling its economy, land, marine and air crossings. Keywords: Central bank, Palestinian Monetary Authority, Palestinian currency. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ : Bu araştırma, Filistin hükümetinde Filistin’e ait para basılmasının önemi ve bunun çok sayıda çabalarla ekonomik sabitlenme için olan acil gereksinimi üzerindedir. Filistin parasını basılması, halen daha, USD, NIS, Euro ve Ürdün Dinarı gibi diğer ülke para birimleriyle uğraşan Filistin insanları için en önemli bağımsız lık ve kritik meselelerden biridir. Bu çalışma, Filistin ekonomisinde para basılmasının önündeki engeller, sebepler ve faktörleri ortaya koyup, bunların Filistin ekonomik gelişimi üzerindeki genel etkisinin nasıl olduğunu inceler. Derin bir çalışmadan ve analizden sonra, Filistin ekonomisinin, Israil işgali gibi ülkenin genel ekonomisini etkileyen faktörler dâhilinde incelenmesi, bu faktörler sonucu ortaya çıkan ve Filistin ekonomisinin gelişmesi önündeki engeller ile Filistin insanların ilerleme, gelişme ve dengesini engelleyen faktörler altında daha detaylı bir inceleme ve daha ileri bir araştırma tavsiye edilmektedir. Bu konuyu okuyucular için aydınlığa kavuşturmak adına, Filistin Parasal Sistemi’nin kısa bir tarihi belirtilen terimlerin anlaşılır olabilmesi için gereklidir. Bunlardan birincisi; faktörlerin, ekonomik ve finansal durumların ve ayrıca Filistin Ulusal Para Sistemi süreci içindeki basit bileşenlerin kullanılabilirlik derecesi ikincisi, Filistin Para Sistemi sürecinde oluşabilecek engel, korku ve uyarıların bilinmesi üçüncüsü ise, Filistin parasal politikalarını, zorunlu İsrail dönemi boyunca belli açıdan ve Filistin Ulusal Otorite sistemi döneminde farklı bir açıdan belirlemektir. Bu çalışmada araştırmacı, finansal ve ekonomik faktörler gibi belirli eksikliklerin önemli hususlarını ve buna ek olarak İsrail işgali altında ekonomi,toprak, deniz ve hava sahasının kontrol altında olduğu Filistin’de para çıkarılmasındaki bileşenleri ortaya koymuştur. Anahtar kelimeler: Merkez Bankası Filistin Para Otoritesi, Filistin Para.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2014. Supervisor: Assist. Prof. Dr. Eralp Bektaş.
Keywords: Banking and Finance; Monetary policy - Palestine; Money Economics - Currency - Palestine; Palestinian Economy; Central Bank, Palestinian Monetary Authority, Palestinian Currency